PENGARUH CAPITAL INTENSITY, UKURAN DEWAN KOMISARIS DAN INVENTORY INTENSITY TERHADAP AGRESIVITAS PAJAK - Alhafiz, Muhammad; Fitriyah (Publika Citra Media, 2025)
This study aims to analyze the effect of Capital Intensity, Board of Commissioners Size and Inventory Intensity on Tax Aggressiveness. This type of research is Quantitative with secondary data sources. The population in this study are industrial sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The sample selection method used in this study was purposive sampling so that the final sample obtained was a sample of 12 companies. Research shows that Capital Intensity, Board of Commissioners Size and Inventory Intensity affect Tax Aggressiveness. Then partially shows that Capital Intensity, Board of Commissioners Size and Inventory Intensity have no significant effect on Tax Aggressiveness.